The Cambridge handbook of bilingual processing - Schwieter, John W., 1979- (Cambridge : Cambridge University Press, 2015)
How does a human acquire, comprehend, produce and control multiple languages with just the power of one mind? What are the cognitive consequences of being a bilingual? These are just a few of the intriguing questions at the core of studying bilingualism from psycholinguistic and neurocognitive perspectives. Bringing together some of the world's leading experts in bilingualism, cognitive psychology and language acquisition, The Cambridge Handbook of Bilingual Processing explores these questions by presenting a clear overview of current theories and findings in bilingual processing. This comprehensive handbook is organized around overarching thematic areas including theories and methodologies, acquisition and development, comprehension and representation, production, control, and the cognitive consequences of bilingualism. The handbook serves as an informative overview for researchers interested in cognitive bilingualism and the logic of theoretical and experimental approaches to language science. It also functions as an instrumental source of readings for anyone interested in bilingual processing.
Second language constructions: usage-based acquisition and transfer Nick Ellis, Ute mer and Matthew O'Donnell; 11. Variability in bilingual processing: a dynamic approach Wander Lowie and Kees de Bot; Part IV. Comprehension and Representation: 12. Conceptual representation in bilinguals: the role of language specificity and conceptual change Panos Athanasopoulos; 13. Emotion word processing within and between languages Jeanette Altarriba and Dana Basnight-Brown; 14. Orthographic processing in bilinguals Walter van Heuven and Emily Coderre; 15. Bilingual lexical access during written sentence comprehension Ana Schwartz; 16. Cross-language interactions during bilingual sentence processing Paola Dussias, Amelia Dietrich and Álvaro Villegas; Part V. Production: 17. Individual differences in second language speech production Judit Kormos; 18.
Title from publisher's bibliographic system (viewed on 01 Feb 2016).
Keywords: Bilingualism -- Handbooks, manuals, etc; Education, Bilingual -- Handbooks, manuals, etc; Language acquisition -- Handbooks, manuals, etc; Second language acquisition -- Research; Language and languages -- Research